Exploring the relationship between social demographic factors and anxiety in college students - Joyce Olushola Ogunrinde; Patrick Dang; Luiza Martins; Nimra Niazi-Galindo; Omolola Adepoju; LaDessa Y. Mitchell (Journal of Affective Disorders Reports)
Introduction: Untreated anxiety increases risk for depression and disruption in college matriculation. Thirty seven percent of college students experience anxiety, but the role of intersectional social identities in providing patient center support is unclear. We conducted a quantitative study of college students to identify the social identities salient to their anxiety risk to optimize mental health support post pandemic. Methods: The GAD- 7 was administered online to 584 US college students from Fall 2020 to Fall 2021. A binary outcome indicated whether students experienced significant anxiety (GAD-7 score ≥15). Independent variables include race/ethnicity, biological sex, age, sports involvement, college level, relationship status, and social class. Descriptive statistics were computed using frequencies and proportions. Bivariate between each independent variable and the outcome of interest were examined using chi-square tests. Multivariate logistic regression was used to assess the strength of the relationships while controlling for all independent variables. Results: The key finding is that lower socioeconomic class was associated with higher risk of anxiety. Conclusion: While no significant interaction effect was seen with the other demographic variables, the high number of women in the study suggests that further investigation is needed into the intersectional effects of gender and class. Moreover, 76 % of participants reported not engaging in sport which suggests sport is an underutilized coping mechanism for reducing anxiety and can serve a possible intervention tool.